Tempos de angústia e desamparo: um estudo de I Tessalonicenses como contribuição para a juventude universitária cristã - Menezes, Joás de Souza (2013)
This work aims to analyze the profile of Brazilian Youth Christian University, aiming to highlight, in the first part, from current researches, the main topics of interest for such young people in contemporary society: university, job, religion, consumption and insecurity. In the second part, it is proposed that a careful reading of the Bible can help university students meet the challenges of these issues. Then, we present some methods of Bible interpretation, considering that they are valuable tools to avoid distortions or reductions of Scripture reading. After that, it presents a brief summary of the historical-critical method and historical-grammatical and sociological reading, psychological reading of bibliodrama and Lectio Divina, in order to demonstrate, in general, the models of biblical interpretation. In the third part, an youth applied analysis model is presented: one pericope in I Thessalonians, whose authorship is attributed to Paul. The goal is doing an exercise of interpretation, besides demonstrating the relevance of Pauline thoughts. Analyzes also, in this research also analyzes the way philosopher Martin Heidegger interpreted this Pauline letter. The object is to establish a dialogue between the Pauline thought and the challenges faced by University Young Christians nowadays.